Varying degrees of perception-action coupling and anticipation in handball goalkeeping - Huesmann, K.; Loffing, F.; Büsch, D.; Schorer, J.; Hagemann, N. (Journal of Motor Behavior, 2022)
Anticipation in sports is commonly investigated using perception-action uncoupled methods, thus raising questions regarding transferability of findings to the field. The aim of this study was to investigate the influence of different degrees of perception-action coupling on anticipation in handball goalkeeping. Advanced, intermediate and novice handball goalkeepers watched videos of throws on the goal and were asked to anticipate throw direction via key press (perception-action artificial condition) and via natural movement response (perception-action simulated condition). Results reveal overall superior performance in the artificial compared to the simulated condition. Skill-based differences, however, were descriptively more pronounced in the simulated condition compared to the artificial condition. The findings further highlight the importance of more representative research methods to unravel perceptual-cognitive skill in sports.